Analysis of the kinetics of phase and amplitude gratings recorded in azopolymer films - Freschi, A. A. [UNESP]; Cortes, A. D S [UNESP]; Donatti, D. A. [UNESP] (AIP Publishing, 2008)
In this work we use a stabilized holographic technique to study both refractive index and absorption gratings recorded in thin films made of Disperse Red 1 (DR1) embedded in an organic polymer matrix (PMMA) deposited on glass substrate. Gratings are recorded by linearly polarized illumination with the interference pattern of two crossing beams. One of the beams is phase modulated and the interference signals between the transmitted and diffracted waves are detected by a tuned lock-in amplifier. The technique allows measuring separately changes of the refractive index and the absorption coefficient during the course of the photoreaction process. The time evolution of the diffraction efficiencies during recording has shown bi-exponential kinetics for both gratings. © 2008 American Institute of Physics.